Hubungan Hasil Belajar Teori Musik Dasar Dan Praktek Instrumen Perkusi Di Jurusan Sendratasik - Kiki Devista Yudha; Jagar Lumbantoruan (SENDRATASIK UNP, 2020)
This study aims at finding out the correlation between learning outcomes in music theory subject and percussion instrument practice subject in the Department of Drama, Dnace and Music Arts. This quantitative research used a correlational method involving two variables, i.e. the learning outcomes of music theory subject and the learning outcomes percussion instrument practice subject. The population in this study was the students of Department of Drama, Dance and Music Arts, Faculty of Languages and Arts, Universitas Negeri Padang whi took Music Theory subject in the even semester of 2017-18 academic calendar. Meanwhile, the sample in this study was the students of the Department of Drama, Dance and Music Arts who took the Percussion Instrument Practice subject in the even semester of 2018-19 academic calendar. The data of this study were documentation of the students’ learning outcomes in music theory and percussion instrument practice subjects which were processed using the Pearson product moment correlation test method. The results of data analysis showed that the value of the correlation test was 0.1013 or 10.13%. This coefficient value was based on the interpretation of the coefficient values in the range 0.00 – 0.19, indicating that the level of correlation between music theory subject and percussion instrument subject was very weak. Using a significance test with an error level of 5%, the results of the hypothesis testing showed that rcount ˂ rtable, indicating that Ha was accepted and Ho was rejected. This means that there is a correlation between the learning outcomes of music theory subject in its application to the practice of percussion instrument, but in a very weak level.